Reform of Labor Wage Determination Provisions: Review of Welfare and Importance in the Job Creation Law - Chelsea Mutiara Putri; Annisa Khairiyah Hutapea; Zaky Ihsan Edy Ramadhani (Mahadi: Indonesia Journal of Law, 2023)
The passing of the Job Creation Law by the government is considered to show more partiality to investors or entrepreneurs and marginalizes labor rights, especially in terms of wages, Indonesia's goal to create and guarantee community welfare in accordance with the concept of the Welfare State (Welfare State) adopted becomes blurred.  This article focuses on the discussion related to the first the determination of the minimum wage submitted to the authority of the Governor and by referring to the economic growth of the Regions and inflation conditions of each Region. Second, the Decent Living Needs (KHL) is no longer an indicator of determining the minimum wage for workers. Third, the abolition of sectoral minimum wages previously in the Manpower Law. This article uses the Juridical-Normative research method. This article found that the Economic growth and inflation rate of each region / province vary. Thus the Minimum Wage cannot be equated between people in each region. In an effort to realize equality of position for employers, Law No. 6 of 2023 has denied the state's obligation to protect workers' rights, thus clashing with Article 27 paragraph (2) of the 1945 Constitution. The policy of abolishing the sectoral minimum wage in the Job Creation Law will cause inequality between sectors and cause a sense of injustice for workers.